Network flow model for microfiltration = Model sieciowy mikrofiltracji - Domański, Zbigniew; Ciesielski, Mariusz; Baran, Bożena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The flow of particles suspended in fluids and transported through different geometries is a process with numerous applications. Realistic filters have randomly-interconnected channel space with complex flow path. However, in micro-fluidic systems, channel space may resemble two-dimensional (2D) tessellation. Here we adopt the network flow concept to analyze 2D micro-filters and study the filter efficiency and the clogging time.
Keywords: mikrofiltracja; sprawność filtracji; blokowanie filtrów; model sieciowy; clogging time; filter efficiency; microfilter